Targeting TL1A and DR3: the new frontier of anti-cytokine therapy in IBD - Bamias, Giorgos; Menghini, Paola; Pizarro, Theresa T; Cominelli, Fabio (Gut, 2025)
TNF-like cytokine 1A (TL1A) and its functional receptor, death-domain receptor 3 (DR3), are members of the TNF and TNFR superfamilies, respectively, with recognised roles in regulating innate and adaptive immune responses; additional existence of a decoy receptor, DcR3, indicates a tightly regulated cytokine system. The significance of TL1A:DR3 signalling in the pathogenesis of inflammatory bowel disease (IBD) is supported by several converging lines of evidence.To provide a comprehensive understanding of what is currently known regarding the TL1A/DR3 system in the context of IBD.TL1A and DR3 are expressed by cellular subsets with important roles for the initiation and maintenance of intestinal inflammation, serving as potent universal costimulators of effector immune responses, indicating their participation in the pathogenesis of IBD. Recent evidence also supports a homoeostatic role for TL1A:DR3 via regulation of Tregs and innate lymphoid cells. TL1A and DR3 are also expressed by stromal cells and may contribute to inflammation-induced or inflammation-independent intestinal fibrogenesis. Finally, discovery of genetic polymorphisms with functional consequences may allow for patient stratification, including differential responses to TL1A-targeted therapeutics.TL1A:DR3 signalling plays a central and multifaceted role in the immunological pathways that underlie intestinal inflammation, such as that observed in IBD. Such evidence provides the foundation for developing pharmaceutical approaches targeting this ligand-receptor pair in IBD.